Respuestas

2013-08-21T02:42:34+02:00
a)
(2 + 3) + 5 = 10
(5 + 3) + 2 = 10
b)
(-3 + 4) + 5 = 6
(4 + 5) – 3 = 6
c)
(7 + 8) + 15 = 30
(8 + 15) + 7 = 30
d)
(5 + 7) + (-2 + 8) = 18
(5 + 8) + (-2 + 7) = 18
e)
(23 + 95) + 35 = 153
(35 + 23) + 95 = 153
f)
(2 * 3) * 5 = 30
(3 * 5) * 2 = 30
g)
(7 * 8) * 2 = 112
(2 * 7) * 8 = 112
 
h)
(5 * 4) * 3 = 60
(3 * 4) * 5 = 60
 
i)
(9 * 7) * 4 = 252
(7 * 4) * 9 = 252
j)
(8 * 5) * 3 = 120
(5 * 3) * 8 = 120
k)
(5 * 3) * 4 = 60
(3 * 4) * 5 = 60
l)
(9 * 7) * 6 = 378
(6 * 7) * 9 = 378
m)
(5 * 7) * 3 = 105
(3 * 7) * 5 = 105